Webster's unabridged dictionary of the English language (New York : Gramercy Books, 1994)
This dictionary continues, in magnificent form, the noble tradition exemplified by Benjamin Franklin of describing and reporting the English Language.
The "A Dictionary of the English Language" section of this book is based on the first edition of The Random House dictionary of the English language, the unabridged edition, 1983.
Includes bibliographical references.
ne 05/10/2021
Ref.
Keywords: English language